PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA MELALUI BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING (STUDI PADA PEGAWAI SEKRETARIAT DPRD DIY) - DHIMAS MUSTIKA UAMI MUSTIKA UTAMI (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to determine the effect of transformational leadership style on organizational culture on the secretariat staff of DPRD DIY, to know the influence of organizational culture on job satisfaction at the secretariat staff of DPRD DIY, to know the influence of transformational leadership style to job satisfaction at the secretariat staff of DPRD DIY, style of transformational leadership, to job satisfaction through organizational culture as intervening variable on the secretariat staff of DPRD DIY.This research uses accidental method, and the population is all secretary of Yogyakarta Regency parliament (DPRD) secretary which is 65 employees, and samplel 55 employees. Methods of data collection by using questionnaires, while the technique of data analysis using path analysis.The result of the research shows that (1) transformational leadership have positive and significant effect on organizational culture α = 0,05 (p = 0,000) (2) organizational culture have positive and significant effect to job satisfaction α = 0,05 (p = 0,000) 3) transformational leadership have positive and significant effect to job satisfaction α = 0,05 (p = 0,000) (4) transformational leadership have positive and significant influence to job satisfaction through organizational culture as intervening α = 0,05This study aims to determine the effect of transformational leadership style on organizational culture on the secretariat staff of DPRD DIY, to know the influence of organizational culture on job satisfaction at the secretariat staff of DPRD DIY, to know the influence of transformational leadership style to job satisfaction at the secretariat staff of DPRD DIY, style of transformational leadership, to job satisfaction through organizational culture as intervening variable on the secretariat staff of DPRD DIY.This research uses accidental method, and the population is all secretary of Yogyakarta Regency parliament (DPRD) secretary which is 65 employees, and samplel 55 employees. Methods of data collection by using questionnaires, while the technique of data analysis using path analysis.The result of the research shows that (1) transformational leadership have positive and significant effect on organizational culture α = 0,05 (p = 0,000) (2) organizational culture have positive and significant effect to job satisfaction α = 0,05 (p = 0,000) 3) transformational leadership have positive and significant effect to job satisfaction α = 0,05 (p = 0,000) (4) transformational leadership have positive and significant influence to job satisfaction through organizational culture as intervening α = 0,05 Keywords: Transformational Leadership on Keja's Satisfaction through Organizational Culture as Intervening Variable.